Detection of GRBs and OTs by All-Sky Optical and SID Monitors - R. Hudec; M. Spurny; M. Krizek; P. Pata; R. Slosiar; M. Rerabek; M. Klima (Advances in Astronomy)
We report on two alternative simple methods to detect counterparts of cosmic gamma-ray bursts (GRBs) and optical transients (OTs). We report on the development and tests of an alternative optical all-sky monitor recently tested at the Karlovy Vary Observatory. The monitor is based on a Peleng 8 mm fish-eye lens (1 : 3,5–1 : 16) and CANON EOS 350D digital CCD camera. This type of monitor represents a low-cost device suitable for easy replication and still able to detect brighter optical transients simultaneously to GRB triggers. Such OTs have been observed for some of the GRBs such as GRB990123, GRB060117, or recently GRB080319 indicating that some fraction of GRBs can generate optical transient emission accessible by simple small aperture instrumentation as described here. These efforts are accompanied by development of dedicated programmes to access and to evaluate all-sky images; these efforts will be also briefly described. The All-Sky Monitor is a space variant optical system and its point spread function (PSF) has not uniform shape in the field of view. The processing and measuring of image data is complicated, and sophisticated deconvolution algorithms are used for image restoration. The second method is the GRB detection based on their ionospheric response.